Isolation of α-glucosidase enzyme inhibitor from titanus (Leea aequata L.) - Bangar, Roy; Ningsih, Kurnia Nastira; Kartasasmita, Rahmana Emran; Insanu, Muhamad (Institut Teknologi Bandung, 2024)
Diabetes mellitus is a metabolic disease characterized by high blood glucose levels. Indonesia was ranked fourth globally, with over 12 million people suffering from diabetes. Natural-based drugs can be an alternative for treating diabetes with fewer side effects and are expected to be more economical than conventional drugs. One of the plant families used to reduce blood glucose levels is the Vitaceae family. One of the Vitaceae species currently used for traditional medicine is Leea aequata. This study aimed to isolate active compounds with α-glucosidase inhibitor activity from titanus plant. This study began with collecting leaf, fruit, and stem samples from titanus plants that grow in North Sumatra. The extraction method used was maceration using ethanol 96%. The isolation stage started with fractionation, followed by purification with column chromatography, in which TLC monitored for each process. α-glucosidase in testing was carried out on extracts, fractions, and isolates using a reagent Multiscan microplate reader at 400 nm. Compound identification was done using spectrodensitometry and 1H-NMR spectroscopy. The IC50 value of the ethyl acetate fraction (2.4±0.02 µg/mL) was higher than the ethanol extract (8.96 ± 0.44 µg/mL), n-hexane fraction (21±0.61 µg/mL), and water fraction (16.96 ± 0.38 µg/mL), so it was continued to the isolation stage. The isolated compound was characterized as 3,3′,4′,5,7-Pentahydroxyflavone 3-rhamnoside (quercitrin) with the IC50 was 12.25 ± 0.2 µg/mL.